2016
DOI: 10.1039/c6an00200e
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell mass spectrometry with multi-solvent extraction identifies metabolic differences between left and right blastomeres in the 8-cell frog (Xenopus) embryo

Abstract: Single-cell metabolic mass spectrometry enables the discovery (untargeted) analysis of small molecules in individual cells. Using single-cell capillary electrophoresis high-resolution mass spectrometry (CE-HRMS), we recently uncovered small-molecule differences between embryonic cells located along the animal–vegetal and dorsal–ventral axes of the 16-cell frog (Xenopus laevis) embryo, raising the question whether metabolic cell heterogeneity also exists along the left–right body axis. To address this question,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 66 publications
2
93
0
2
Order By: Relevance
“…These developments enabled femtogram (zeptomole) limit of detection (38) for protein digests from cell populations. For example, we recently developed metabolomic CE microflow electrospray ionization (ESI) HRMS platforms (26) for measuring metabolites (27,39) and proteins (36) in single Xenopus blastomeres. Using microdissection to isolate single blastomeres, tandem mass tags to enable multiplexing quantification, and bottom-up proteomics, CE-ESI-HRMS was able to quantify 130 -150 different protein groups (isoforms) in common between multiple single blastomeres in the 16-cell Xenopus embryo.…”
mentioning
confidence: 99%
“…These developments enabled femtogram (zeptomole) limit of detection (38) for protein digests from cell populations. For example, we recently developed metabolomic CE microflow electrospray ionization (ESI) HRMS platforms (26) for measuring metabolites (27,39) and proteins (36) in single Xenopus blastomeres. Using microdissection to isolate single blastomeres, tandem mass tags to enable multiplexing quantification, and bottom-up proteomics, CE-ESI-HRMS was able to quantify 130 -150 different protein groups (isoforms) in common between multiple single blastomeres in the 16-cell Xenopus embryo.…”
mentioning
confidence: 99%
“…This process is best understood in frog embryos, but has also been observed and functionally implicated in amphioxus [149], sea urchin [146,150,151], C. elegans [152 -154], zebrafish [96,155,156] and recently humans [157,158]. Indeed, a recent analysis of the differences between blastomeres at the very earliest stages of embryo development identified distinct metabolites in L versus R cells in the eight-cell embryo using mass spectrometry [88]. The majority of these metabolites themselves have roles in functional regulation of ion transport [159 -167], suggesting possible feedback loops in electrophysiology that could be important amplifying mechanisms for initially subtle LR asymmetry.…”
Section: Physics Upstream and Downstream Of Transcriptional Networkmentioning
confidence: 99%
“…From data in a range of model species, it is clear that numerous aspects of development, including maternal protein localization [84,[95][96][97], Wnt signalling [98] and small signalling molecules [88], are already consistently asymmetric long before cilia appear: most animal embryos can tell their left from their right at very early stages. Thus, the search for the origin of asymmetry has been extended far upstream of neurulation [22,99].…”
Section: Physics Upstream and Downstream Of Transcriptional Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…mechanosensitive cilia, morphogen gradients or vesicular particles. More recent studies have shown that primary cilia are not in fact calcium-responsive mechanosensors [8], and that asymmetries in cleavage-stage frog embryos have not only consistently asymmetric metabolic profiles [9], but also protein components with functional roles in asymmetry development [10]. Consistent with the existence of L/R asymmetry at such an early stage of development, Dasgupta and Amack [6] used mosaic cell labelling and time-lapse imaging in the zebrafish embryo to demonstrate that ciliated cells within Kupffer's vesicle-a structure that is functionally analogous to the embryonic node and alternatively termed the 'L/R organizer'-are non-stochastically arranged, suggesting that they may be propagating L/R positional information that exists prior to L/R Organizer morphogenesis and hence, generation of directional fluid flow.…”
Section: Synopsis Of Laterality Chaptersmentioning
confidence: 99%